2021
DOI: 10.3390/nano11020425
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Ferulic Acid Antioxidant Activity by Multiple Emulsions: In Vitro and In Vivo Evaluation

Abstract: Ferulic acid is a derivative of cinnamic acid showing efficacious anti-oxidant activity. It catalyzes the stable phenoxy radical formation, upon absorption of ultraviolet light, giving the strength to ferulic acid for terminating free radical chain reactions. Ultraviolet rays are one of the most dangerous factors that daily assault the skin, causing excessive generation of reactive oxygen species (ROS), which are regarded to be important contributors to a variety of cutaneous alterations. The skin possesses en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 46 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…24,25 Ferulic acid shows an antioxidant activity due to the phenolic ring and unsaturated side chain. 12 It has the capacity to inhibit a complex reaction of free radicals generation, by forming stable phenoxyl radicals, in the reaction of the radical molecule with the molecule of antioxidant. The phenoxy radical is formed, which is highly resonance stabilized, so it ends its life in condensation and collision with another ferulate radical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Ferulic acid shows an antioxidant activity due to the phenolic ring and unsaturated side chain. 12 It has the capacity to inhibit a complex reaction of free radicals generation, by forming stable phenoxyl radicals, in the reaction of the radical molecule with the molecule of antioxidant. The phenoxy radical is formed, which is highly resonance stabilized, so it ends its life in condensation and collision with another ferulate radical.…”
Section: Discussionmentioning
confidence: 99%
“…11 After oral administration, the bioavailability of ferulic acid in the skin is relatively low. 12 Formulas enriched with ferulic acid gain several times higher antioxidant and photoprotective efficacy than those without it. The effectiveness of ferulic acid, as a strong antioxidant reducing UV-induced oxidative skin damage, as well as inhibiting the formation of hyperpigmentation and accelerating skin regeneration, has been proved in numerous studies on cell cultures of fibroblasts, keratinocytes, and melanocytes.…”
mentioning
confidence: 99%
“…In addition, the plant phenolic acid 4-coumaric acid protected against oxidative DNA damage in rat colonic mucosa and ultraviolet B-induced oxidative DNA damage in rabbit corneal-derived cells [ 36 , 37 ]. Ferulic acid exhibits a variety of pharmacological properties, such as antioxidant [ 38 , 39 ], ameliorating the pulmonary fibrosis [ 40 ], alleviating the acute liver injury [ 41 ] and lipid-lowering effect [ 42 ]. Astragalin and afzelin were the natural flavonoids and found in various herbal medicinal plants such as Cuscuta chinensis [ 43 ]; modern pharmacological researches have shown that astragalin carried out antioxidant and anti-inflammatory activity through the regulation of NO, malondialdehyde (MDA), reactive oxygen species (ROS), superoxide dismutase (SOD), glutathione peroxidase (GSH-Px), catalase (CAT), tumor necrosis factor- α (TNF- α ), interleukin 6 (IL6), and inducible nitric oxide synthase (iNOS) [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan–ferulic–bovine serum albumin microcapsules, obtained by the spray-drying technique, demonstrated high thermal stability and in vitro sustained release; thus, they may find application as carriers in novel functional foods, as well as in drug delivery systems [ 88 ]. Dermal absorption of ferulic acid delivered in the form of stable w/o/w emulsions with antioxidant properties was developed by the team of Mancuso et al [ 89 ]. The formulation proved capable to treat UV-B-induced erythema.…”
Section: Novel Strategies For Ferulic Acid Drug Deliverymentioning
confidence: 99%